Insect species composition in eggplant cultivation with special emphasis on life cycle and management of eggplant borer, Leucinodes orbonalis Guenee - Abdulbaqi, Rostaee (2021)
The eggplant (Solanum melongena L.), is an important vegetable in Malaysia with the total cultivation area of 2407 ha and a total production of 39311 tonnes. There is a lack of information on the study of insects associated with eggplant cultivation in Malaysia. The knowledge on this subject matter is important in order to have a comprehensive knowledge on the insect pests and beneficial insects in the eggplant cultivation. Special emphasis is given to the eggplant shoot and fruit borer (Leucinodes orbonalis Guenée) as it is the major pest that causes serious damage to the fruits that will cause economic loss. The best combination of control methods to control L. orbonalis is also highly needed. Therefore, this study was conducted i) to investigate the insect species composition associated with eggplant; ii) to determine the life cycle and morphological description of L. orbonalis; and iii) to determine the best combination of control methods for L. orbonalis. Four types of Insects sampling were conducted in the organic experimental farm namely visual observation, sweep netting, pitfall trap dan yellow sticky trap. For life cycle study, L. orbonalis was cultured in insect laboratory. All stages of life cycle were studied. The experiment on the control methods of eggplant borer comprised of six treatments and laid out in a randomized complete block design (RCBD) with three replications. The effects of six treatments on infestation rate of L. orbonalis were studied. A total of 15786 specimens comprised of 136 morphospecies belong to 72 families under 11 orders were recorded. Out of total, 71 morphospecies were pests that belong to three groups of feeding habit namely sap-feeder, leaf-feeder and fruit borer. There were 65 morphospecies composed of four functional groups viz predators, parasitoids, pollinators and omnivores. The abundance of insects among the orders were significantly different (F = 91.42, d.f = 10, 154; P < 0.05). Hemiptera was recorded to be the most abundant order (309.29 ± 40.87). Sap-feeders was significantly (p<0.05) most abundant group (307.81 ± 40.92) compared to the others. Life cycle study of L. orbonalis showed that the incubation period was 5.5 ± 0.09 days, larval period was 12.06 ± 0.19 days undergoing five larval instars and pupal stage took 10.36 ± 0.10 days. The mean longevity of adult female was 5.40 ± 0.15 days whereas adult male was 4.45 ± 0.11 days. The life cycle of female and male moth was 33.32 ± 0.53 days and 32.37 ± 0.49 days, respectively. On average, each female produced 174 ± 22.01 eggs with the sex ratio female to male was 2:1. The result showed that a combination of chemical and mechanical controls (chlorantraniliprole 8.77% W/W + thiamethoxam 17.54% W/W + yellow sticky trap + hand picking) was the most effective as the lowest shoot infestation (0.53 ± 0.13%) and maximum healthy fruit (25.42 ± 0.89 t ha-1 ) was recorded. Result of this research may be helpful to plan an effective pest management strategy.